In search of enhanced material: Kalanchoe ×toelkenii (Crassulaceae subfam. Kalanchooideae), a new South African nothospecies derived from Kalanchoe ×gunniae × K. sexangularis - Smith, Gideon F. (Phytotaxa, 2023)
Considerable investment in the breeding of enhanced material of Kalanchoe (Crassulaceae subfam. Kalanchooideae) has resulted in several new nothospecies introduced from South Africa, all of which provide additional horticultural possibilities, especially under irrigation-limited conditions. Kalanchoe ×toelkenii, derived from K. ×gunniae back-crossed with K. sexangularis, is described here as a further large-growing nothospecies with improved inflorescence spread and floral density.